2013
DOI: 10.1007/s12262-013-1004-3
|View full text |Cite
|
Sign up to set email alerts
|

Subtrochanteric Fractures: Comparison of Proximal Femur Locking Plate and Intramedullary Locking Nail Fixation Outcome

Abstract: Fixation of subtrochanteric fracture, even for experienced surgeons, is a challenge. This fracture is most difficult to treat, and the incidence of complications in this type of fracture is higher. This study compared surgical results of two methods, proximal femur locking compression plate and intramedullary locking nail. This is an analytic study, performed on all patients with subtrochanteric fracture who were referred to the hospital during 3 years. They were treated with proximal femur locking plate or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…To achieve a successful treatment, the clinical, anatomical and biomechanical characteristics of the region must be well known [3,6]. Although these fractures are seen in all age groups, they are mostly seen in elders with low energy injuries (falling) and in young people with high energy injuries (traffic accident or falling from a high level) [2]. In our study, the number of high energy trauma was 14, and low energy trauma was 22.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…To achieve a successful treatment, the clinical, anatomical and biomechanical characteristics of the region must be well known [3,6]. Although these fractures are seen in all age groups, they are mostly seen in elders with low energy injuries (falling) and in young people with high energy injuries (traffic accident or falling from a high level) [2]. In our study, the number of high energy trauma was 14, and low energy trauma was 22.…”
Section: Discussionmentioning
confidence: 59%
“…Unstable proximal femur fractures are difficult entities even for experienced surgeons [2]. To achieve a successful treatment, the clinical, anatomical and biomechanical characteristics of the region must be well known [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result concurred with studies. In 2013 Mirbolook, Babak Siavashi, Adel et al [13] concluded that the results of pertrochanteric fracture fixation by intramedullary or locking plate were similar and had the same outcome. Neither treatment has statistically significant difference in complications, onset of complications incidence, and time of full-weight bearing.…”
Section: Discussionmentioning
confidence: 99%